REDESIGN KURSI BUS YANG ERGONOMIS DENGAN PENDEKATAN ANTROPOMETRI (STUDI KASUS BUS TRANS METRO DEWATA) - I Gusti Ngurah Priambadi; Ni Luh Putu Lilis Sinta Setiawati; I Made Dwi Budiana Penindra; Mia Juliana; Ni Made Cyntia Utami; Krisna, I Gusti Ngurah Bagus Hermaya (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2023)
Due to passenger complaints regarding the comfort of the seats on the Trans Metro Dewata Bus, and the possibility that the design of the seats could result in musculoskeletal disorders (MSDs), it is deemed necessary to redesign the seats of the Trans Metro Dewata Bus to create an ergonomic seat design. In the process of redesigning the bus seats, the ergonomics method with an anthropometric approach was used. The ergonomic approach in question is to adjust the seat design to the anthropometric dimensions of the sample of Trans Metro Dewata Bus passengers. In this anthropometric approach, four anthropometric dimensions are determined which play an important role in chair redesign, namely (1) shoulder height, (2) knee fold (popliteal), (3) hip width, and (4) distance from knee fold (popliteal) to buttocks. For each dimension, calculations were carried out according to the procedure for 100 sample data that had been taken from passengers of the Trans Metro Dewata Corridor 3 Bus in March 2023. Based on the passenger samples that had been obtained, then the anthropometric data testing process was carried out starting from the normality test, uniformity test data, and data adequacy test.